Ultrasensitive Temperature Sensing Based on Ligand‐Free Alloyed CsPbClxBr3−x Perovskite Nanocrystals Confined in Hollow Mesoporous Silica with High Density of Halide Vacancies. Issue 46 (13th October 2021) - Huang, Yipeng; Lai, Zhiwei; Jin, Jingwen; Lin, Fangyuan; Li, Feiming; Lin, Longhui; Tian, Dongjie; Wang, Yiru; Xie, Rongjun; Chen, Xi
Abstract: Temperature sensing based on fluorescent semiconductor nanocrystals has recently received immense attention. Enhancing the trap‐facilitated thermal quenching of the fluorescence should be an effective approach to achieve high sensitivity for temperature sensing. Compared with conventional semiconductor nanocrystals, the defect‐tolerant feature of lead halide perovskite nanocrystals (LHP NCs) endows them with high density of defects. Here, hollow mesoporous silica ( h ‐SiO2 ) template‐assisted ligand‐free synthesis and halogen manipulation (chloride‐importing) are proposed to fabricate highly defective yet fluorescent CsPbCl1.2 Br1.8 NCs confined in h ‐SiO2 (CsPbCl1.2 Br1.8 NCs@ h ‐SiO2 ) for ultrasensitive temperature sensing. The trap barrier heights, exciton–phonon scattering, and trap state filling process in the CsPbCl1.2 Br1.8 NCs@ h ‐SiO2 and CsPbBr3 NCs@ h ‐SiO2 are studied to illustrate the higher temperature sensitivity of CsPbCl1.2 Br1.8 NCs@ h ‐SiO2 at physiological temperature range. By integrating the thermal‐sensitive CsPbCl1.2 Br1.8 NCs@ h ‐SiO2 and thermal‐insensitive K2 SiF6 :Mn 4+ phosphor into the flexible ethylene–vinyl acetate polymer matrix, ratiometric temperature sensing from 30.0 °C to 45.0 °C is demonstrated with a relative temperature sensitivity up to 13.44% °C −1 at 37.0 °C. The composite film shows high potential as a thermometer for monitoring the body temperature. This work demonstrates the unparalleled temperature sensing performance of LHP NCs and provides new inspiration on switching the defects into advantages in sensing applications. Abstract : Ligand‐free CsPbCl x Br3− x NCs confined in hollow mesoporous silica (CsPbCl x Br3− x NCs@ h ‐SiO2 ) with high density of halide vacancy defects are rationally designed for ultrasensitive temperature sensing. The ratiometric sensing system consisting of the thermal sensitive CsPbCl x Br3− x NCs@ h ‐SiO2 and K2 SiF6 :Mn 4+ reference shows outstanding temperature resolution, which is promising for body temperature sensing.